2017
DOI: 10.18632/oncotarget.21260
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic management and one-year outcomes in elderly patients with acute coronary syndrome

Abstract: BackgroundElderly represents a subgroup of high-risk ACS patients due to their advanced age and other comorbidities. Unfortunately, they are also often under-represented in many studies and clinical trials. Furthermore, cardiologists commonly find difficulties in the choice of the antiplatelet treatment and even on whether invasive revascularization should be used. In this study, the management of elderly ACS patients regarding antiplatelet therapy and revascularization procedures will be analyzed.Methods1717 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 28 publications
3
5
1
8
Order By: Relevance
“…Impaired left ventricular function and higher incidence of acute heart failure justify the higher rate of using loop diuretic and mineralocorticoid receptor antagonist in the older group. Older patients were less treated invasively; these results were supported by prior studies including GRACE and ROSAI-2 registries [ 13 , 24 27 ]. Many factors contribute to less referral for catheterization in older patients with NSTE-ACS like associated comorbidities, especially anaemia and CKD, higher rate of bleeding complications and the more presentation with haemodynamic instability in this population [ 13 ].…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Impaired left ventricular function and higher incidence of acute heart failure justify the higher rate of using loop diuretic and mineralocorticoid receptor antagonist in the older group. Older patients were less treated invasively; these results were supported by prior studies including GRACE and ROSAI-2 registries [ 13 , 24 27 ]. Many factors contribute to less referral for catheterization in older patients with NSTE-ACS like associated comorbidities, especially anaemia and CKD, higher rate of bleeding complications and the more presentation with haemodynamic instability in this population [ 13 ].…”
Section: Discussionsupporting
confidence: 73%
“…Older patients were less treated invasively; these results were supported by prior studies including GRACE and ROSAI-2 registries [ 13 , 24 27 ]. Many factors contribute to less referral for catheterization in older patients with NSTE-ACS like associated comorbidities, especially anaemia and CKD, higher rate of bleeding complications and the more presentation with haemodynamic instability in this population [ 13 ]. Furthermore, there are contradictory results with respect to prognostic benefit of routine invasive strategy in the elderly with NSTE-ACS, MOSCA and Italian Elderly ACS trials [ 28 , 29 ], which are two randomized controlled trials that showed no difference between invasive and conservative strategies in the elderly with NSTE-ACS in terms of recurrent MI, cardiovascular rehospitalization and mortality.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Elderly patients are frequently under‐represented in clinical trials, mainly very elderly patients (older than 80 years old) and the information about efficacy and safety of medical therapies and interventional procedures is unknown 14 ; Indeed, elderly patients are less likely to receive evidence‐based therapies 15 . In the LONGEVO‐SCA registry, we observed AF patients received less evidence‐based therapy after an ACS, especially frail AF patients with only 78% of prescription of aspirin and 60.9% of OAC after discharge (both P < .001).…”
Section: Discussionmentioning
confidence: 99%